(untitled) (Research, Society and Development, 2021)
Social justice has never been so much in vogue as in this epidemic scenario of COVID-19, the inequalities were accentuated and publicized in different media, presenting the diverse effects in specific groups and contexts, due to associated factors to socioeconomic inequalities, due to racist, misogynistic, xenophobic and homolesbotransphobics among others. The proposed dossier will receive contributions in Portuguese, English and Spanish on the problematization of Education for Social Justice, identifying praxis related to race and traditional peoples, gender, sexual orientation, sexuality, refugees and immigration processes from perspectives such as critical racial theory (CRT), intersectionalities, decolonialities, feminist studies, anti-racism and others pedagogies that contribute to social transformation and construction of an education for democracy and, consequently, a more equitable society